Genotype-Phenotype Correlations in Charcot-Marie-Tooth Disease Due to MTMR2 Mutations and Implications in Membrane Trafficking - Wang, Haicui; Kaçar Bayram, Ayşe; Sprute, Rosanne; Ozdemir, Ozkan; Cooper, Emily; Pergande, Matthias; Efthymiou, Stephanie; Nedic, Ivana; Mazaheri, Neda; Stumpfe, Katharina; Azizi Malamiri, Reza; Shariati, Gholamreza; et al. (Frontiers in Neuroscience, 2019)
Charcot-Marie-Tooth type 4 (CMT4) is an autosomal recessive severe form of neuropathy with genetic heterogeneity. CMT4B1 is caused by mutations in the myotubularin-related 2 (MTMR2) gene and as a member of the myotubularin family, the MTMR2 protein is crucial for the modulation of membrane trafficking. To enable future clinical trials, we performed a detailed review of the published cases with MTMR2 mutations and describe four novel cases identified through whole-exome sequencing (WES). The four unrelated families harbor novel homozygous mutations in MTMR2 (NM_016156, Family 1: c.1490dupC; p.Phe498IlefsTer2; Family 2: c.1479+1G>A; Family 3: c.1090C>T; p.Arg364Ter; Family 4: c.883C>T; p.Arg295Ter) and present with CMT4B1-related severe early-onset motor and sensory neuropathy, generalized muscle atrophy, facial and bulbar weakness, and pes cavus deformity. The clinical description of the new mutations reported here overlap with previously reported CMT4B1 phenotypes caused by mutations in the phosphatase domain of MTMR2, suggesting that nonsense MTMR2 mutations, which are predicted to result in loss or disruption of the phosphatase domain, are associated with a severe phenotype and loss of independent ambulation by the early twenties. Whereas the few reported missense mutations and also those truncating mutations occurring at the C-terminus after the phosphatase domain cause a rather mild phenotype and patients were still ambulatory above the age 30 years. Charcot-Marie-Tooth neuropathy and Centronuclear Myopathy causing mutations have been shown to occur in proteins involved in membrane remodeling and trafficking pathway mediated by phosphoinositides. Earlier studies have shown by the rescue of MTM1 myopathy by MTMR2 overexpression, emphasizing the importance of the phosphoinositides equilibrium. This proved that the regulation of expression of these proteins involved in the membrane remodeling pathway may compensate each other’s loss or gain-of-function mutations by restoring the phosphoinositides equilibrium. This provides a potential therapeutic strategy for the defects of the membrane remodeling pathway leading to neuromuscular diseases.